Body fat is related to poor motor skills and physical fitness in socially assisted children and adolescents regardless of age, sex, and lean soft tissue - Saraiva, Bruna Thamyres Ciccotti [UNESP]; Diniz, Tiego Aparecido; Agostinete, Ricardo Ribeiro [UNESP]; Tebar, William Rodrigues [UNESP]; dos Santos, Amanda Barbosa [UNESP]; Christofaro, Diego Giulliano Destro [UNESP] (Elsevier, 2025)
Objective: To analyze the relationship between body fat (BF), motor skills, and physical fitness in children and adolescents. Methods: In total, 216 children and adolescents (143 males and 73 females, aged 5–15 years) from a social project composed this study. Body mass and height were measured to calculate the body mass index (BMI). DXA was used to estimate the percentage of BF and lean soft tissue. The Körperkoordinationstest für Kinder (KTK) was used to assess motor skills (jumping sideways test corresponds to speed, walking backwards to balance, and moving sideways to laterality), modified pull-ups to measure upper limb strength and the 1-mile run/walk test to estimate maximal oxygen uptake. Results: In the unadjusted models, BF was a significant negative predictor for almost all motor skills and physical fitness variables measured; jumping sideways (β = −0.168, 95%CI = −0.402; 0.039), walking backwards (β = −0.010, 95%CI = −0.011; −0.008), modified pull-ups (β = −0.045, 95%CI = −0.052; −0.037), and 1-mile run/walk (β = −0.18, 95%CI = −0.39; −0.06), but not moving sideways (β = −0.05, 95%CI = −0.12; 0.05). In the model considering sex and age, the significance remained the same as in the model without adjustment. When we added lean soft tissue to these adjustments, all variables were significant; jumping sideways (β = −0.544, 95%CI = −0.834; −0.253), walking backwards (β = −0.007, 95%CI = −0.010; −0.004), modified pull-up (β = −0.020, 95%CI = −0.028; −0.013), 1-mile run/walk (β = −0.386, 95%CI = −0.505; −0.267), and moving sideways (β = −0.07, 95%CI = −0.14; −0.01). Conclusion: In children and adolescents from a socially assisted background, BF was negatively related to motor skills and physical fitness, regardless of age, sex, and lean soft tissue.
Keywords: Body composition; Muscle strength; Overweight; Postural balance